Colour Management for Applications Using Thermochromic Inks - Kashtalyan, Katsiaryna (Univerzita Pardubice, 2014)
The objective of the thesis is to offset a two-component antifraud pattern with thermochromic and conventional inks achieving maximal colour match between the parts by means of colour management. The theoretic part comprises the information about colour spaces, colour management and thermochromic inks. Herein the questions of an ICC profile creation and evaluation, colour management workflow arrangement are studied, the structure and properties of thermochromic inks are considered. The experimental part describes the performed research, including the steps: the first test chart creating and printing, colour measuring, printing press ICC profile generating, performing the thermochromic ink overprint simulation by applying the profiles in ColorLab software application, creating and printing the second test chart, colour measuring and final evaluation of the profiles. According to the results, the maximal colour match was achieved for thermochromic overprints over two-component combinations of primary yellow-cyan and yellow-pink inks with area coverage 10?60 of either constituent. Better outcome was obtained for the line graphics.
Správa barev pro oblast termochromních barev
Keywords: správa barev; ICC profily; barvová odchylka; termochromní barvy; colour management; ICC profiles; colour difference; thermochromic inks